EFFECTIVENESS OF CRIMINAL LAW ENFORCEMENT ON HAZARDOUS AND TOXIC WASTE POLLUTION (B3) - Ikama Dewi Setia Triana; Eti Mul Erowati (Ganesha Law Review, 2024)
This study aims to determine how the implementing legal provisions and utilization of forest land conversion into plantations are oriented towards capitalism. This study uses a normative legal research method with the types of approaches, namely the legislative approach and the conceptual approach. The legal materials used are primary, secondary, and tertiary legal materials, obtained by conducting a literature study. The results of the study indicate that law enforcement against violations related to B3 waste still faces various significant obstacles. One of the main obstacles is the weak supervision by the responsible authorities, such as the Ministry of Environment and Forestry and related agencies at the regional level. Suboptimal supervision is often caused by limited human resources and technology that supports the monitoring process of companies or industries that produce B3 waste. This causes some violations to go undetected or not followed up properly. In addition, limited law enforcement facilities and infrastructure are also inhibiting factors. The lack of adequate laboratories to test waste samples, obsolete environmental quality monitoring equipment, and minimal budget to support supervision and investigation operations causes the effectiveness of law enforcement to be low. Law enforcers such as police, prosecutors, and judges who handle environmental cases often do not have sufficient knowledge or technical expertise about the impacts and characteristics of B3 waste, so that the case handling process does not run optimally.The sanctions given to perpetrators of pollution have also not provided a sufficient deterrent effect.